Polar Similars: Using Massive Mobile Dating Data to Predict Synchronization and Similarity in Dating Preferences - Levy, Jon; Markell, Devin; Cerf, Moran (Frontiers in Psychology, 2019)
Leveraging a massive dataset of over 400 million potential matches between single heterosexuals on a leading mobile dating application we were able to identify numerous characteristics of effective matching. Effective matching is defined as the exchange of contact information with the intent to meet in person. The characteristics of effective match include alignment of psychological traits (i.e. extroversion), physical traits (i.e. height), personal choices (i.e., the relationship type they desired), and shared experiences. For nearly all characteristics, the more similar the individuals were the higher the likelihood of them finding each other desirable and opting to meet in person. The only exception was introversion, where introverts rarely had an effective match with other introverts. Additionally, we investigated the preliminary stages of the choice process. We looked at the consistency between the choice of men/women, the time it took users to make these binary choices and the tendency of yes/no decisions. We used a biologically-inspired choice model to estimate the time allotted to a decision and could predict the decision and response time with nearly 60% accuracy. Given that people make their initial selection within no more than 11 seconds and ultimately converge to a partner who shares numerous attributes with them, we suggest that users are less selective in their early preferences and gradually converge to clusters with high degree of similarity in characteristics during their conversation.